Draw 50 buildings and other structures : the step-by-step way to draw castles and cathedrals, skyscrapers and bridges, and so much more ... - Ames, Lee J. (New York : Watson-Guptill Publications, 2013)
Shows young aspiring artists how to draw dozens of buildings, helping to develop their technical skills and build a repertoire of subjects, particularly those relating to architecture.
Keywords: Architectural drawing -- Technique -- Juvenile literature; Buildings in art -- Juvenile literature; Drawing -- Technique -- Juvenile literature